Analysis of Socio Economic Status of Tribals and Pig Husbandry Practices in Kolli Hills, Namakkal District of Tamil Nadu, India - Vigneshwaran, S; Ramesh, V; Sivakumar, K; Singh, D Anandha Prakash; Ramakrishna, S; Chinamanai, K (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was carried out to analyse the socio economic status of tribals and their involvement in agriculture and animal husbandry activities with special reference to pig husbandry practices. The results revealed that most of the farmers belong to scheduled tribes (97.40 per cent) and were educated at primary level school education (58.78 per cent). It was observed that majority of farmers (58.33 per cent) were having an annual income less than Rs. 30,000. Among the animal husbandry activities dairy contributed the major sector in the study area. Analysis of pig husbandry practices revealed that, all the respondents reared the desi pigs for fattening purpose and not for breeding purpose. Majority of farmers reared the pigs in open shed and followed swill feeding. Most of the farmers did not follow any deworming and vaccination to their pigs. Pigs were marketed at 80 to 90 kg body weight at the rate of Rs. 90 to 100 per kg live weight.